Upaya Guru dalam Menanamkan Nilai Toleransi Terhadap Peserrta Didik di Sekolah SMA Negeri 2 hibala - Paulinus Kanisius Ndoa; Kristiana Mendrofa; Andrius Sarumaha (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The purpose of this writing is to explain that the importance of the value of tolerance that can be developed in learning is carried out by the teacher. One of the values ​​instilled in children is the value of tolerance. Instilling the value of tolerance to students includes; responsibility, honesty, compassion, caring and cooperation, self-confidence, creativity, justice and leadership, kind and humble, and tolerance, peace-loving and unity. The method used in this paper uses qualitative methods by finding and collecting observational data, interviews, documentation and data analysis techniques. The results of research on several matters related to the teacher's efforts in instilling tolerance values ​​for students indicate that the teacher's role in instilling tolerance values ​​for students includes designing learning strategies, having optimal and proportional competence and having a strong commitment in setting an example to children regarding One of the character values ​​is the tolerance value. Because it is still found that in general they have obstacles in tolerance, namely there is still a lack of self-awareness from students of the importance of tolerance, and there are still several parties who do not participate and work together. The teacher's role in instilling the value of tolerance can also be through learning activities using several methods such as setting an example, helping each other, and respecting each other.